Empowering or Replacing? A Systemic Functional Linguistic Analysis of Anies Baswedan’s Discourse on AI in Education - Syafrayani, Putri Rizki (Universitas Muhammadiyah Sumatera Utara, 2025)
The rapid integration of Artificial Intelligence (AI) in education has generated global debates over whether technology empowers or replaces human educators. This study analyzes the ideological construction of AI in Indonesian educational discourse through Anies Baswedan’s public statements using Systemic Functional Linguistics (SFL) and Critical Discourse Analysis (CDA) frameworks. Drawing on ten segments from Baswedan’s 2025 thread on X (formerly Twitter), the study examines linguistic patterns across ideational, interpersonal, and textual metafunctions to uncover how language encodes power relations, values, and policy orientations. The findings reveal a consistent rhetorical balance between technological optimism and humanistic caution. Baswedan’s use of contrastive structures (e.g., “bukan alat kendali, tapi alat bantu”), inclusive pronouns (“kita,” “mari”), and metaphors of journey and balance constructs an ideology of regulated progress—positioning AI as a supportive instrument rather than an autonomous agent. His discourse promotes participatory governance, moral education, and human-centered innovation, aligning with UNESCO’s (2023) principles of ethical AI while diverging from efficiency-driven global models. However, the analysis also exposes limitations, including the absence of concrete policy mechanisms to address structural inequities and commercial influences in AI implementation. This research contributes to the growing body of Global South scholarship on AI and education, demonstrating how political leaders linguistically negotiate the tensions between technological advancement and cultural preservation. It underscores the need for locally grounded, ethically informed approaches to AI integration that preserve human agency and educational integrity.